Notebook from China ; Moments of Play - Leth, Jorgen; Holmberg, Dan (Danish Film Institute, 2008)
Notebook from China (1987): In an interesting documentary, director Jorgen Leth rides the Chinese rail system through 6,000 miles of cities, towns, and countryside with both nature and human activity highlighted. Noodle-makers and jugglers, fishmongers and women cyclists, performers and their audiences are all poetically and imaginatively noted and photographed. The only noticeable omission is any information on the images that pass so evocatively in front of the camera. [All Movie Guide]
Keywords: DVD-Video